In silico characterization of plasmodial transketolases as potential malaria drug target - Boateng, Rita Afriyie (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2018)
Expected release date-April 2019
Keywords: Uncatalogued